A Comparative Of The Maximum Aerobic Speed Mas Among Handball Players Of The Excellent Division , According To The Playing Positions - Benaissa, Fayssal; Karfes , Nabil (sports creativity, 2025)
The study aimed to identify the differences in the maximal aerobic speed )MAS ( between the handball players of the excellent Division by playing positions in order to answer the question of whether there is statistically significant differences in the maximal aerobic speed )MAS (between the handball players of the excellent division by playing positions? We have assumed that there are statistically significant differences in the )MAS) between the handball players of the excellent division by playing position, we have adopted in our study the descriptive approach appropriate to the nature of the topic, Applied to a sample consisted of 44 players from the excellent division the sample chosen by Stratified random and we used the 30-15 IFT Martin Buchheit test as a tool after making sure of the scientific foundations of validity, reliability and objectivity. After the statistical treatment we reach to that there are no differences in the maximal aerobic speed)MAS( between the handball players of the excellent division by playing positions. Key Words:: maximal aerobic speed )MAS(, playing position , handball Abstract: The study aimed to identify the differences in the maximal aerobic speed )MAS ( between the handball players of the excellent Division by playing position in order to answer the question of whether there is statistically significant differences in the maximal aerobic speed )MAS (between the handball players of the excellent division by playing position? We have assumed that there are statistically significant differences in the )MAS) between the handball players of the excellent division by playing position, we have adopted in our study the descriptive approach appropriate to the nature of the topic, Applied to a sample consisted of 44 players from the excellent division the sample chosen by Stratified random and we used the 30-15 IFT Martin Buchheit test as a tool after making sure of the scientific foundations of validity, reliability and objectivity. After the statistical treatment we reach to that there are no differences in the maximal aerobic speed)MAS( between the handball players of the excellent division by playing position